The Use of Technology in Teaching and Learning (Case Study in Two State Schools in Kupang, Indonesia during the COVID-19 Pandemic) - Seprianus A. Nanotek; Naniana N. Benu (Randwick International of Education and Linguistics Science Journal, 2022)
This article is an exposition and analysis based on a case study of two public schools in Kupang city. Data were obtained through observations and questionnaires distributed to teachers who teach at the schools. The results show that learning continues even though the pandemic of COVID-19 forces learning to take place virtually. Teachers have no difficulty in delivering teaching materials to their students because of the availability of technology along with its various applications and features. In this situation, teachers find new challenges in managing learning. However, there are various obstacles that contribute to the effectiveness of learning. These obstacles come from students and technical infrastructure which is also a problem for teachers. The findings in this study were analyzed from five aspects, namely pedagogical, the mastery of technology, human resource readiness, economic, and social aspects. All these aspects are interrelated, therefore intervention from all stakeholders is needed to realize learning in an effective virtual classroom environment.